Social Media Marketing Internship at Prabhu Logistics - Parmar, Hitesh (ATLAS SkillTech University, 2024)
In this report, the summer internship experience at Prabhu Logistics India Private Limited is detailed, where the privilege of being a Summer Trainee in the dynamic field of Marketing and Advertising was experienced. As a student specializing in Marketing & Advertising and Marketing in S.Y.M.B.A, the fascination with the world of marketing, particularly in the Advertising sector, has always been present. This internship provided a valuable opportunity to gain practical insights into marketing strategies, branding efforts, and the ground-level workings of the Advertising industry.
Project Report on Social Media Marketing Internship at Prabhu Logistics (2022-24) Under the Guidance of Prof. Tapish Panwar
Keywords: Marketing & Advertising; Marketing; Logistics; Advertising sector